Down-Regulation of LOC645166 in T Cells of Ankylosing Spondylitis Patients Promotes the NF-κB Signaling via Decreasingly Blocking Recruitment of the IKK Complex to K63-Linked Polyubiquitin Chains - Yu, Hui-Chun; Huang, Kuang-Yung; Lu, Ming-Chi; Huang Tseng, Hsien-Yu; Liu, Su-Qin; Lai, Ning-Sheng; Huang, Hsien-Bin (Frontiers in Immunology, 2021)
Ankylosing spondylitis (AS) is a chronic inflammatory disease that mainly affects the spine. AS is highly associated with the expression of HLA-B27. Up to 95% AS patients are HLA-B27-positive. However, only 1-2% of the HLA-B27-positive carriers suffer from AS, implying that other factors may also govern the development of AS. Long non-coding RNAs (lncRNAs) can regulate the immune response via their binding proteins. In the present study, we have identified that the levels of lncRNA, LOC645166, in T cells of AS patients were reduced. Overexpression of LOC645166 in Jurkat cells down-regulated the IL-23p19 expression and suppressed the JAK2/STAT3 signaling in response to treatment of phorbol 12-myristate 13-acetate. In order to explore the role of LOC645166 in the pathogenesis of AS, RNA pull-down assay plus proteomic approach and western blotting were performed and identified that LOC645166 prefers binding the K63-linked polyubiquitin chains. LOC645166 can suppress recruitment of the IKK complex to K63-linked polyubiquitin chains and diminish IKK2 activation, leading to down-regulation of NF-kappa B activation. Down-regulation of LOC645166 expression in T cells of AS patients up-regulates NF-kappa B activation via decreasingly impeding recruitment of the IKK complex to K63-linked polyubiquitin chains, allowing AS patients to exhibit more sensitivity to stimulation by the proinflammatory cytokines or by TLR ligands.